2020
DOI: 10.1002/mma.6669
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study of boundary layer flow of viscous incompressible fluid past an inclined stretching sheet and heat transfer using nonpolynomial spline method

Abstract: In the present paper, we study the boundary layer flow of viscous incompressible fluid over an inclined stretching sheet with body force and heat transfer. Considering the stream function, we convert the boundary layer equation into nonlinear third-order ordinary differential equation together with appropriate boundary conditions in an infinite domain. The nonlinear boundary value problem has been linearized by using the quasilinearization technique. Then, we develop a nonpolynomial spline method, which is use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Due to emergence of numerical techniques, many researchers have investigated numerical methods and solved these type of problems in different variants with or without heat transfer. Moreover, a few studies are available in literature (see [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] ). Natural porous media fluxes include processes such as the movement of oil, gas, or moisture in hydrocarbons, as well as the potential deployment of methane in gas hydrates,the movement of Waterless Phase Liquids in polluted groundwater, the movement of fluids and soluble compounds in living organisms materials, and the dissolving metamorphism of ice are all examples of natural porous media and mechanisms although some illustrations of industrial porous media and the procedures that correspond to them are: drying of paper pulp, the soaking of liquids in nappies and other items with a same uptake capacity, the treatment of gas and water in fuel cells, and the drying of foods.…”
Section: Introductionmentioning
confidence: 99%
“…Due to emergence of numerical techniques, many researchers have investigated numerical methods and solved these type of problems in different variants with or without heat transfer. Moreover, a few studies are available in literature (see [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] ). Natural porous media fluxes include processes such as the movement of oil, gas, or moisture in hydrocarbons, as well as the potential deployment of methane in gas hydrates,the movement of Waterless Phase Liquids in polluted groundwater, the movement of fluids and soluble compounds in living organisms materials, and the dissolving metamorphism of ice are all examples of natural porous media and mechanisms although some illustrations of industrial porous media and the procedures that correspond to them are: drying of paper pulp, the soaking of liquids in nappies and other items with a same uptake capacity, the treatment of gas and water in fuel cells, and the drying of foods.…”
Section: Introductionmentioning
confidence: 99%
“…In literature review, it appears that heat transfer in natural convection power law non‐Newtonian fluid flow through vertical truncated wavy cone with the Tiwari and Das 22 nanofluid model has not yet been investigated. However, several overlapping studies in one or other way can be found in previous studies 23–41 . In order to fill the gap in literature, the thermally stratified boundary layer CNT–water nanofluid flow suspended by a vertical truncated cone is considered.…”
Section: Introductionmentioning
confidence: 99%
“…However, several overlapping studies in one or other way can be found in previous studies. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] In order to fill the gap in literature, the thermally stratified boundary layer CNT-water nanofluid flow suspended by a vertical truncated cone is considered. Firstly, the system gives a nonsimilar solution; then it converts to a similar solution by using transformation to find its solution.…”
mentioning
confidence: 99%